A study of clinical profile of primary extranodal lymphomas in a tertiary care institute in South India - Ananth Pai; Thiruvengadasamy Kannan; R G Balambika; Vindhya Vasini (Indian Journal of Medical and Paediatric Oncology)
Context: Primary extranodal lymphoma (pENL) refers to group of disorders arising from tissues other than lymph nodes. The incidence of pENL is increasing and is probably due to better diagnostic immunophenotyping and imaging modalities. Hence, this study was undertaken to ascertain the incidence, distribution, and histological subtypes of extranodal non-Hodgkin lymphoma (NHL) in a tertiary care institute in South India. Subjects and Methods: This was a retrospective study of patients diagnosed to have histologically proven NHL. The demographic and clinical features, laboratory parameters, imaging findings, histopathology, and immunophenotyping were documented. The lymphomas were grouped as extranodal and nodal. The data were tabulated in a Microsoft Excel sheet, and descriptive analysis was done. Results: Primary extranodal NHLs constituted 35.96% (41/114) of all NHLs. The B symptoms were less common in pENL compared to nodal NHL. Gastrointestinal tract (GIT) constituted the most common extranodal site (19/41, 46.34%), and diffuse large B-cell lymphoma (DLBCL) was the most common histological subtype. Majority (40/41, 97%) of the patients with pENL were immunocompetent. 31/41 (75%) patients were in Stage I–II compared to 58/73 (79.4%) patients in Stage III–IV in nodal NHL. Conclusions: Primary extranodal NHL constituted about one-third of patients diagnosed to have NHL at our center with the GIT being the most common site of presentation and DLBCL being the most common histology. A strong suspicion of NHL at an extranodal site with appropriate pathological and immunophenotyping evidence is needed to establish the diagnosis of a pENL.